Body appreciation in British men: Correlates and variation across sexual orientation. (December 2018) - Alleva, Jessica M.; Paraskeva, Nicole; Craddock, Nadia; Diedrichs, Phillippa C.
Highlights: Body appreciation among British men positively correlated with physical activity. Body appreciation was inversely linked to conformity to masculine norms and comparisons. Body appreciation was lower among sexual minority compared to heterosexual men. Social comparison tendencies mediated this relationship. Athletic appearance-ideal internalisation also mediated this relationship. Abstract: Investigations of positive body image among men and across various social identities are lacking, and could contribute to a more complete understanding of the construct, including how positive body image can be improved. This study addressed this gap by investigating correlates of body appreciation – a key facet of positive body image – in men, and testing whether levels of body appreciation vary across sexual orientation. Data from a British community sample of 439 men ( M age = 39.13) showed that body appreciation inversely correlated with conformity to masculine norms and upward appearance-based social comparisons, and positively correlated with physical activity. Body appreciation was lower among sexual minority compared to heterosexual men, and athletic appearance-ideal internalisation and upward appearance-based social comparisons mediated this relationship. Replicating prior research among men, body appreciation positively correlated with body satisfaction, and inversely correlated with perceived appearance pressures from media and eating pathology. These findings have implications for interventions addressing body image among men.